Biocontrol of Rhizome Rot Disease of Ginger (Zingiber officinale Rosc.) - Khatso, Kevimeo; Tiameren, N. Ao (International Journal of Bio-resource and Stress Management, 2023)
The efficacy of some biological control agents were tested for their antagonistic ability against Fusarium oxysporum f.sp zingiberi both in vitro and in vivo. Among the biological control agents assayed, Trichoderma viride (68.3%) and Trichoderma harzianum (66.7%) exhibited the maximum mycelial growth inhibition in dual culture under in vitro. Under field condition, seed treatment with T.viride @ 4g 10 ml-1 of water kg-1 of seed resulted in maximum reduction in plant mortality (4.2.%) with consequent increase in disease control (84.9%), plant stand over control (32.8.%), plant height (48.9 cm), number of tillers (18.0) and yield (10.5 kg plot-1), respectively.